2018
DOI: 10.2147/cmar.s185350
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the Glasgow prognostic score in colorectal cancer: a meta-analysis of 9,839 patients

Abstract: PurposeThe aim of this study was to perform a systematic review and meta-analysis to evaluate the value of the Glasgow prognostic score (GPS) or modified Glasgow prognostic score (mGPS) in patients with colorectal cancer (CRC).MethodsA comprehensive medical literature search was performed using the online databases PubMed, Embase, Web of Science, and the Cochrane Library. After extracting basic characteristics and prognostic data from the included studies, overall survival (OS) and cancer-specific survival (CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 66 publications
1
39
0
Order By: Relevance
“…There is increasing evidence to suggest that the elevation of some clinical inflammatory factors predicts prognoses in tumor patients, and that combinations of inflammatory factors further improves the efficacy of prognosis prediction. The NLR, lymphocyte to monocyte ratio (LMR), and Glasgow prognostic score (GPS) have been reported to be associated with clinical outcomes in patients with various cancers (Kubo et al, 2016;Lu et al, 2019;Tan et al, 2018). Recently, Jafri, Shi & Mills (2013).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence to suggest that the elevation of some clinical inflammatory factors predicts prognoses in tumor patients, and that combinations of inflammatory factors further improves the efficacy of prognosis prediction. The NLR, lymphocyte to monocyte ratio (LMR), and Glasgow prognostic score (GPS) have been reported to be associated with clinical outcomes in patients with various cancers (Kubo et al, 2016;Lu et al, 2019;Tan et al, 2018). Recently, Jafri, Shi & Mills (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although there was no significant association between [ 18 F]FDG uptake of BM and hemoglobin level, hematopoiesis of red blood cells might confound [ 18 F]FDG uptake of BM [17,21,25]. Finally, because of the retrospective nature of the study, we could not assess the relationship of [ 18 F]FDG uptake of BM with the other well-known prognostic factors for systemic inflammatory response such as the Glasgow prognostic score which has been found to be associated with poor prognosis in patients with malignant diseases including breast cancer [43,44]. Therefore, further prospective studies with laboratory as well as histopathologic results are needed to elucidate the connection between BM metabolism on PET/CT and systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer progression is associated with a high level of systemic inflammation [37]. Many studies have shown that serum inflammatory markers, such as C-reactive protein (CRP) [38][39][40], the NLR [41][42][43], the platelet-tolymphocyte ratio [44,45], the Glasgow Prognostic Score (GPS) [46,47], and the systemic immune-inflammation index [48,49], are related to the clinical outcomes of cancer patients. Low body weight and hypoproteinemia are also both associated with persistent systemic inflammation [50][51][52], and the BMI and ALB have also been confirmed as effective prognostic markers for cancer patients [53,54].…”
Section: Discussionmentioning
confidence: 99%